Pengaruh Good Corporate Governance terhadap Nilai Perusahaan dengan Corporate Social Responsibility sebagai Variabel Intervening pada Perusahaan Sektor Energi yang terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Nurfianti, Salsya; Simatupang, Frido Saritua (J-MAS (Jurnal Manajemen dan Sains), 2024)
The study aims to find out the impact of good corporate governance, which includes institutional ownership, board of commissioners size and board of directors size, on corporate value (PBV), with corporate social responsibility as an intervening variable, on energy sector companies listed in the IDX in 2019-2022. This research uses quantitative methods. The sampling technique uses purposive sampling of as many as 13 samples of energy sector companies. The data analysis method used is descriptive analysis, using path analysis using Eviews 12, and data has passed the classic assumption test. The results of the research showed that, in part, institutional ownership and the size of the board of commissioners had a positive and significant influence on the price to book value. in part, the size of the board of directors had a negative and significant impact on the price to book value. And the letter, corporate social responsibility, is unable to mediate the influence of institutional ownership, the board of commissioners, and the board of directors on price to book value.